TRADISI MOOI INDIE DALAM IMAJI FOTOGRAFI KARTU POS INDONESIA - Nofrizaldi Nofrizaldi (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2023)
The visualization of postcards with mountain as the photo objects, rice fields framed in a natural scene becomes a very interesting thing to be observed. The objects, that usually become the favorite of a painting with indie Mooi style, are then adapted by photographer in a postcard sheet. Seeing the phenomenon, the author questioned why photographers still maintain the images that have been explored by the art of painting, to be re-production into the work of photography. It is interesting to examine, especially from the visual aspect with descriptive interpretive approach, by making an interpretation of what is seen, heard and understood, so it is expected to create diverse views on an existing problem.This study resulted a conclusion that, in terms of the needs of art lovers, the need for imaging Mooi indie when it is viewed from the perspective of tourists or foreign tourists, it is still very high. Travelers or foreign tourists need evidence that their journey to Indonesia - a tropical country with abundant light - is real. Photos in this case are powerful entities in the role of proof of existence. As a young artist from the heirs of culture and eastern artworks that have a high history and aesthetics in the context of tradition, Mooi Indie should begin to be abandoned and photo artists embark on an odyssey that puts forward newness or local wisdom in the work.